Digitalization of Instructions on Labor Protection and Safety Techniques - Rakhimov Oktyabr Dustkabilovich,; Muradov Sirojiddin Husan o`g`li, (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the digital economy and its advantages, the necessity and importance of the application of digital technologies in the field of labor protection, as well as the advantages. Brief information about the digitization model of training and testing of employees' knowledge of labor protection and safety techniques developed by the authors and its content is given